2022
DOI: 10.1016/j.amp.2021.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress, emotion regulation and quality of life during the Covid-19 outbreak: A multi-cultural online survey

Abstract: The present COVID-19 epidemic is a threat to physical health and brings a drain to Quality of life and mental health in the general population. However, changes in Quality of life and mental health status due to pandemic-related is less known. This study was implemented to investigate and predict changes in the Quality of life and psychological changes in people worldwide due to the pandemic. 3002 individuals participated in an online survey. The result showed that Quality of life is significantly decreased ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 16 publications
2
24
0
3
Order By: Relevance
“…The present results are consistent with previous research performed during the COVID-19 pandemic. A recent multi-cultural study showed that self-reported quality of life decreased over time, while perceived stress level and difficulty with emotion regulation increased significantly during the coronavirus pandemic [24]. Significant changes in stress and life satisfaction were found during the pandemic in various longitudinal studies [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results are consistent with previous research performed during the COVID-19 pandemic. A recent multi-cultural study showed that self-reported quality of life decreased over time, while perceived stress level and difficulty with emotion regulation increased significantly during the coronavirus pandemic [24]. Significant changes in stress and life satisfaction were found during the pandemic in various longitudinal studies [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from various regions of the world indicate that about 50% of people have experienced high stress levels during the coronavirus pandemic [65][66][67][68]. Khodami [24] found that younger people and individuals with a low quality of life were more likely to experience higher stress levels and more significant emotion regulation problems. With increasing quarantine time, quality of life decreased, and perceived stress and emotion regulation problems increased.…”
Section: The Theoretical Background Of the Current Studymentioning
confidence: 99%
“…Since the onset of the pandemic, an important number of studies on its psychological impacts has been published. A majority of those assessed its emotional impacts and showed that, in general, individuals experience a decrease in their quality of life ( Bao, Sun, Meng, Shi, & Lu, 2020 ; Khodami, Seif, Koochakzadeh, Fathi, & Kaur, 2021 ; Porcelli, 2020 ). To summarize main results, Rajkumar ( 2020 ) performed a meta-analysis and showed that mental health during the current pandemic is characterized by increases in anxiety, fear, stress, depression, and sleep disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…The use of adaptive emotion regulation strategies (e.g., acceptance, positive reappraisal) has been linked to higher levels of quality of life and well-being, while the use of non-adaptive ones (e.g., worry/rumination, self-blame) has been related to lower levels of quality of life and well-being ( Balzarotti, Biassoni, Villani, & Velotti, 2016 ; Garnefski & Kraaij, 2007 ). While some studies confirmed the relationship between emotion regulation strategies and quality of life during the COVID-19 pandemic (e.g., Dubey, Podder, & Pandey, 2020 ; Khodami et al, 2021 ), modifications in the use of emotion regulation strategies since the pandemic have not yet been investigated. Consequently, it seems of interest to compare the use of emotion regulation strategies in general to the use of these strategies in the specific pandemic context to investigate their potential evolution when facing such adverse situations.…”
Section: Introductionmentioning
confidence: 99%
“…In a study with a large scope putting forward this negative effect, Al Dhaheri et al (2021) 2021) emphasized that the level of quality of life of all individuals, especially of women, young adults, and unemployed individuals, was affected negatively from this process and showed a decrease. The effect of the COVID-19 on the quality of life of individuals was examined in Africa, North America, Asia, Australia, Europe, and South Africa, and the negative effect of the COVID-19 on the quality of life of individuals was found as high in this study with a comprehensive scope, regardless of the area lived (Khodami et al, 2021). Similar to the findings of this study, studies both in Turkey and in other parts of the world put forward that the quality of life of individuals got affected negatively in the restrictions process of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 71%